Women Representation and Affirmative Action in Nigerian Politics: A Study of The Fourth Republic (1999-2023) - Onimisi, Timothy (Journal of Public Administration and Government, 2025)
Nigeria is one of the countries in Africa with the lowest number of women's representation in politics, despite having a 35% Affirmative Action. Women in Nigeria make up about half of the population and about 51 percent of voters during elections, but in terms of women's representation in the Fourth Republic (1999-2023), it remains low. This study examines the challenges affecting the effective implementation of the 35% Affirmative Action in Nigeria. The research adopted feminism as a theoretical framework and reviews some related literature that are in line with women in politics. The research utilized a combination of survey methods to collect primary quantitative data and secondary research to analyze existing information. The findings revealed that high illiteracy levels among women, cultural and religious beliefs, poverty, and negative perception of women in politics were the major challenges to the effective implementation of the National Gender Policy of 35% Affirmative Action. The paper recommended the need for a gender quota system with constitutional backing and public enlightenment programmes.